2008
DOI: 10.1021/jp8050609
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and Light-Emitting Epoxy Super-Nanocomposites Containing ZnO-QDs/SiO2 Nanocomposite Particles as Encapsulating Materials for Solid-State Lighting

Abstract: Figure SI-1. CIE chromaticity diagram of the LED lamp encapsulated with the epoxy super-nanocomposite containing 5 wt% Z-S nanocomposite particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 30 publications
(73 reference statements)
1
28
0
1
Order By: Relevance
“…31 Silicon oxide (SiO 2 ) has been employed as a shield, with the aim of improving the optical properties and stability of ZnO nanomaterials. [32][33][34][35] Previous studies have reported that SiO 2 -coated ZnO NRs display high sensitivity towards detecting ultraviolet (UV) photons 36 and biomolecules, 37 good UV-durable superhydrophobicity, 38 and enhanced UV emission. 39,40 Conversely, heterogeneous ZnO ND/SiO 2 structures reportedly show enhanced visible emission 41 but negative photoconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…31 Silicon oxide (SiO 2 ) has been employed as a shield, with the aim of improving the optical properties and stability of ZnO nanomaterials. [32][33][34][35] Previous studies have reported that SiO 2 -coated ZnO NRs display high sensitivity towards detecting ultraviolet (UV) photons 36 and biomolecules, 37 good UV-durable superhydrophobicity, 38 and enhanced UV emission. 39,40 Conversely, heterogeneous ZnO ND/SiO 2 structures reportedly show enhanced visible emission 41 but negative photoconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [22] reported the synthesis of ZnO QDs with blue emission by annealing zinc sulfide nanoparticles in air atmosphere at 600 1C. Li et al [23] reported bulk preparation of blue-emitting ZnO-QDs-silica/ epoxy super-nanocomposites by an ultrasonic technique via dispersion of ZnO-QDs/silica nanocomposite particles with a matching refractive index in the transparent epoxy matrix. Chakraborti et al [24] reported the emission spectra of ZnO quantum dots, which were observed in the range of 440-600 nm by bounding with 8-Anilinonaphthalene-1-sulfonic acid and/or lysozyme.…”
Section: Introductionmentioning
confidence: 99%
“…5.15). As hosting matrices, common polymers such as polymethylmethacrylate [229], polystyrene [230], poly(vinylalcohol) [231], and epoxy resins [232,233] as well as specialty polymers such as polynorbornene [234], polyacrylamide [235], polydiacetylene [236], and MEh-PPV copolymers [237] were used. A recent review of hybrid organic-inorganic light-emitting devices was reported by Sessolo and Bolink [238].…”
Section: Light-emitting Devicesmentioning
confidence: 99%